Clinical presentation of posterior cerebral artery occlusions – Clinical rationale for a more aggressive therapeutic strategy? - Volker Maus (Elsevier, 2021)
Introduction: A proximal occlusion of the posterior cerebral artery (PCA) can affect patients severely and clinical outcome might be poor. Aim of this paper is to describe clinical presentation, diagnostic findings and outcome of patients suffering from ischemia in the PCA territory. Methods: We conducted a retrospective analysis of clinically affected patients with imaging-based evidence of ischemia within in the PCA territory at a comprehensive stroke center over a six-year period. Clinical (including demographics, National Institutes of Health Stroke Scale, NIHSS, modified Rankin Sclae, mRS), imaging (including occlusion site and brain infarction) and therapeutic data were evaluated. A favorable outcome was defined as an mRS ≤2. Results: Two hundred thirty-five patients were clinically affected with evidence of PCA ischemia detected by cross-sectional imaging. One-hundred fourty-five patients demonstrated an occlusion of the PCA including 43/145 (30%) with P1 occlusion, 80/145 (55%) with P2 and 22/145 (15%) with P3 occlusion. The most frequent symptom was hemi−/ quadrantanopsia (181/235, 77%). Sixty-eight patients (29%) suffered from hemiparesis. The occurrence of a hemiparesis was associated with a P1 occlusion (27/43, 63% vs. 41/192, 21%; p < 0.0001). Hemi−/quadrantanopsia was less frequently associated with a P1 occlusion (26/43, 61% vs. 155/192, 81%; p = 0.0043). P1 occlusions more frequently showed thalamic infarction (28/43, 65% vs. 65/192, 34%; p < 0.0001). At discharge, patients with P1 occlusion more often showed a poor outcome (mRS > 2, 30/43, 70% vs. 55/192, 29%; p < 0.0001). Conclusion: Hemiparesis due to P1 occlusion is a common phenomenon in stroke patients and associated with a poor clinical outcome.